Judicial decision-making within political parties: A political approach. (September 2019) - Bolleyer, Nicole; von Nostitz, Felix-Christopher; Bormann, Nils-Christian
How do German intra-party tribunals manage internal conflicts? More specifically, why do they accept some cases for trial but reject others? Required by law to strictly adhere to implement rule of law standards, German intra-party tribunals are designed to insulate conflict regulation from politics. Meanwhile, research on judicial politics highlights the role of political and strategic considerations in accepting cases for trial. Building on the latter, we develop a theory that emphasizes tribunals' political concerns such as winning elections. We test our hypotheses with a mixed-effects logit model on a novel data set covering 1088 tribunal decisions in six German parties from 1967 until 2015. Our findings indicate that political factors exert a strong effect on tribunal case acceptance. Tribunals are more likely to accept cases when suffering electoral loss and after losing government office. Moreover, tribunals dismiss cases more easily when their parties display relatively high levels of policy agreement.